Impact of a NDUFC2 Variant on the Occurrence of Acute Coronary Syndromes - Gallo, Giovanna; Migliarino, Serena; Cotugno, Maria; Stanzione, Rosita; Burocchi, Simone; Bianchi, Franca; Marchitti, Simona; Autore, Camillo; Volpe, Massimo; Rubattu, Speranza (Frontiers in Cardiovascular Medicine, 2022)
Background Among several potential mechanisms, mitochondrial dysfunction has been proposed to be involved in the pathogenesis of coronary artery disease (CAD). A mitochondrial complex I deficiency severely impairs cardiovascular health and contributes to CAD development. Previous evidence highlighted a key role of NDUFC2, a subunit of complex I, deficiency in the increased occurrence of renal and cerebrovascular damage in an animal model of hypertension, and of juvenile ischemic stroke occurrence in humans. Furthermore, a significant decrease of NDUFC2 mRNA was detected in peripheral blood mononuclear cells from patients experiencing acute coronary syndrome (ACS). The T allele at NDUFC2/rs23117379 variant is known to associate with reduced gene expression and mitochondrial dysfunction. Objective In the present study we tested the impact of the T/C NDUFC2/rs23117379 variant on occurrence of ACS in a prospective cohort of CAD patients (n = 260). Results Hypertension, smoking habit, diabetes and hypercholesterolemia were present in a large proportion of patients. Non-ST-elevation myocardial infarction (NSTEMI) represented the most frequent type of ACS (44%, n = 115), followed by ST-elevation myocardial infarction (STEMI) (34%, n = 88) and unstable angina (22%, n = 57). The alleles/genotypes distribution for T/C at NDUFC2/rs23117379 revealed that the TT genotype was associated with a trend toward the development of ACS at an earlier age (TT 61 ± 12, CT 65 ± 12 and CC 66 ± 11 years; p = 0.051 after adjustment for gender, hypertension, smoking habit, diabetes and hypercholesterolemia) and with a significant predictive role for ACS recurrence (hazard ratio [HR]1.671; 95% confidence interval [CI], 1.138–2.472; p = 0.009). Conclusions Our findings are consistent with a deleterious effect of NDUFC2 deficiency on acute coronary events predisposition and further support a role of the NDUFC2/rs23117379 variant as a genetic cardiovascular risk factor.